Identification of the fuel rod cladding destruction from the change of the SNF storage casks radiation - Rudychev, V.G.; Azarenkov, N.A.; Girka, I.O.; Rudychev, Y.V. (Вопросы атомной науки и техники, 2020)
Two options for changing the distribution of spent nuclear fuel due to the possible destruction of the cladding of fuel rods, which causes a change in radiation outside the cask, are considered for VSC-24 casks used for storage of spent nuclear fuel by the dry method. The effect of height reduction due to the destruction of the fuel rods of all 24 SFAs and 10 central SFAs on external radiation is studied analytically and by numerical modeling in the MCNP package. The destruction of 24 SFA is shown to lead to a significant decrease in the dose rate of neutrons and gamma-radiation from ⁶⁰Co on the weather lid of the cask, and of gamma-radiation from SNF isotopes at the mid-height of the side surface of the cask. The destruction of the ten central SFAs can be determined only from a change in the neutron radiation in the air inlets of the cask. Для контейнерів VSC-24, які використовують для зберігання ВЯП сухим методом, розглянуто два варіанти зміни розподілу ВЯП внаслідок можливого руйнування оболонок твелів, що спричиняє зміну випромінювання поза контейнером. Аналітичним та чисельним моделюванням у пакеті MCNP досліджено вплив зменшення висоти внаслідок руйнування твелів всіх 24 ВТВЗ та 10 центральних ВТВЗ на зовнішнє випромінювання. Показано, що руйнування 24 ВТВЗ спричиняє значні зменшення (стрибок) потужності дози нейтронів і γ-випромінювання від ⁶⁰Co на погодній кришці контейнера, а для γ-випромінювання від ізотопів ВЯП – на середині висоти бічної поверхні контейнера. Руйнування 10 центральних ВТВЗ визначається лише з випромінювання нейтронів у повітрозабірнику контейнера. Для контейнеров VSC-24, используемых при хранении ОЯТ сухим методом, рассмотрены два варианта изменения распределения ОЯТ вследствие возможного разрушения оболочек твэлов, ведущего к изменению излучения вне контейнера. Аналитическим и численным моделированием в пакете MCNP исследовано влияние уменьшения высоты вследствие разрушения твэлов всех 24 ОТВС и 10 центральных ОТВС на внешнее излучение. Показано, что разрушение 24 ОТВС приводит к значительным уменьшениям мощности дозы нейтронов и γ-излучения от ⁶⁰Co на погодной крышке контейнера, а для γ-излучения от изотопов ОЯТ – на середине высоты боковой поверхности контейнера. Разрушение 10 центральных ОТВС определяется только изменением излучения нейтронов в воздухозаборнике контейнера.